Citrin deficiency mimicking mitochondrial depletion syndrome - Grünert, Sarah; Schumann, A.; Freisinger, P.; Rosenbaum-Fabian, S.; Schmidts, M.; Müller, Amelie Johanna; Beck-Wödl, S.; Haack, T. B.; Schneider, H.; Fuchs, H.; Teufel, U.; Gramer, Gwendolyn; et al. (BMC pediatrics, 2020)
Neonatal intrahepatic cholestasis caused by citrin deficiency (CD) is a rare inborn error of metabolism due to variants in the SLC25A13 gene encoding the calcium-binding protein citrin. Citrin is an aspartate-glutamate carrier located within the inner mitochondrial membrane.